Cheap talk comparisons in multi-issue bargaining - Archishman Chakraborty; Richmond Harbaugh (Claremont McKenna College, Department of Economics, 2002)
Bargaining over two issues as a bundle permits credible cheap talk about their relative importance even when interests are directly opposed on each issue. The resulting communication gains can exceed the gains from bundling previously identified in the monopoly pricing literature.
Keywords: D82; C78; 330; bundling; bargaining; cheap talk; Verhandlungstheorie; Price Bundling; Theorie